Translating Water Fund Payments for Ecosystem Services in the Ecuadorian Andes - Joslin, Audrey (My University, 1905)
As a form of environmental governance, Payments for Ecosystem Services (PES) is imbued with ideological values that can conflict with those of participating rural communities. The discursive frame surrounding PES may be contentious, even if the conservation activities promoted by these initiatives are not. Moving PES into practice therefore requires a process of translation from urban-based practitioners to rural communities. Drawing upon an empirical case study of FONAG, a water fund from Ecuador that is often promoted as the ideal type, this article employs data from participant observation, key informant interviews and textual materials to examine this process of translation. The article focuses particularly on the efforts to negotiate the discourse of PES that move the projects into on-the-ground practice. While Ecuador's political context has softened the emphasis on economically valuing ecosystem services, FONAG uses neoliberal conservation narratives that identify rural poverty as the main cause of environmental degradation and target the reform of local people through economic incentives. To enrol communities, however, intermediaries are needed to translate water fund PES to appeal to local perspectives, values and institutions. The author argues that contrasting narratives of PES can exist simultaneously between the entities that are implementing PES and the targets of that implementation.